A psychoanalytic probe into Academic Othering of the United States: Defenses of splitting and projection, consequences, and alternatives through emotion work. (May 2020) - Ulus, Eda
For this Special Paper Series of Organization, I work with a psychoanalytic perspective to scrutinize organizing processes as critical academics—specifically, unconscious dynamics of responding to US-based social crises. I contend that it is not feasible to organize effectively against the violent hate of right-wing populist movements sustained by Othering without commitment to confronting academics' individual and collective Othering and defensive processes. These defenses include splitting and projecting onto convenient Others, which can serve performative gratifications. Through analysis of critical academic declarations in 2017, I analyze Academic Othering of the United States. Splitting the United States off as the 'bad' Other of the 'good' United Kingdom/European Union/non-United States undermines critical analysis and potential for solidarity and relational concern. Without probing these uncomfortable dynamics, we damage opportunities as elite, privileged academics to make a difference for global struggles, and collude in exclusion. Undertaking emotion work on our academic identities to move away from the defense of splitting, and toward nuance with Klein's depressive position, will support listening to affected voices and extending—not merely performing—concern and care.